Live with passion! [ - Robbins, Anthony (Nightingale-Conant, 1998)
Learn to use quality quantifiers to increase your desire for living; use the power of paradox to launch your plans;replace dormant resources with new assets to improve the quality of your life, and infuse your life with meaning and purpose